Spheres of Influence: A Few Reflections on the Concept - Heino Nyyssönen (Institute of International Studies, Corvinus University, 2022)
In the frame of the Ukrainian crisis the question of spheres of influence has returned to political discourse. This may be an awkward subject, but what if we only deny the existence of such power constellations as spheres of influence? Do spheres of influence exist, or are they relics of history, and mere rhetoric? And if they exist, where can we find them? The hypothesis in this article is that instead of being a tangible reality, spheres of influence are obscure and contested political constructions, which nevertheless can have an impact on political behaviour. To demonstrate this, the article will first introduce a few examples of the current use of the concept. Secondly, a few remarks follow concerning the different IR schools of thought, and conceptual history as a method. Next, the article turns to discussing a few dictionaries and the empirical material for the present inquiry, which consists of recent textbooks, i.e. the current political science curriculum in one particular university, at the University of Tampere, Finland. More empirical cases deal with the division of Africa, the post-WWII situation, and the Hungarian revolution of 1956.